2019
DOI: 10.1108/ijlss-02-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

The application of six sigma to reduce the pre-operative length of hospital stay at the hospital Antonio Cardarelli

Abstract: Purpose The best treatment for femur fractures is the surgical one within 48 h from the admission to the hospital. These fractures have serious consequences, both in terms of morbidity and socio-economic impact. In the hospital A.O.R.N. Cardarelli of Naples in Italy, the mean pre-operative length of hospital stay (LOS) was nine days and just 4 per cent of patients was operated within the suggested time. Therefore, a diagnostic-therapeutic-assistance path (DTAP) was implemented to improve the process. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 61 publications
3
29
1
Order By: Relevance
“…“A. Cardarelli”, as described in [ 30 ]. Among them, the presence of a protocol for the rapid transfer of the patient from the emergency department to the orthopedic ward, timely multi-professional (orthopedic, internal medicine, anesthesiology and nursing) assessment, and, not least, early rehabilitation care, are common points for both the pathways implemented at the hospital Cardarelli of Naples and the hospital Ruggi of Salerno, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…“A. Cardarelli”, as described in [ 30 ]. Among them, the presence of a protocol for the rapid transfer of the patient from the emergency department to the orthopedic ward, timely multi-professional (orthopedic, internal medicine, anesthesiology and nursing) assessment, and, not least, early rehabilitation care, are common points for both the pathways implemented at the hospital Cardarelli of Naples and the hospital Ruggi of Salerno, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the study discusses a comparison between the presented results and those obtained by implementing analogous clinical pathways, with particular focus on the pathway developed at the Italian national hospital A.O.R.N. Cardarelli of Naples, as reported in [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars conducted research on the optimization of patient treatment procedures in hospitals. For example, Ricciardi, C. et al [ 33 ] and Giovanni, I. et al [ 34 , 35 ] applied the Six Sigma method to the patient hospital service, and their research results proved that the service mode combined with the Six Sigma method can improve the efficiency of health management personnel for patients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2 Lean has gained significant attention in the healthcare industry to develop safe, efficient and wastefree operational processes. [3][4][5] Recent studies reported positive results in various healthcare applications, such as reducing patient waiting time and length of hospital stay, 6,7 improved resource utilization and staff satisfaction. 8,9 An important aspect of lean is the waste identification to reduce non-valueadded activities and provide standardized solutions for better performance and operational excellence.…”
Section: Introductionmentioning
confidence: 99%